1993
DOI: 10.1002/syn.890150402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium channel blockers on stimulation‐induced changes in transmitter release at the frog neuromuscular junction

Abstract: We have examined the effects of various calcium channel blockers on stimulation-induced changes in end-plate potential (EPP) amplitude at the frog neuromuscular junction. We found that the addition of small concentrations (1-10 microM) of Cd2+ to the low calcium bathing Ringer reduced both the control EPP amplitude and the increase in EPP amplitude that normally occurs during repetitive stimulation under low quantal conditions. These effects of Cd2+, which developed rapidly following its addition to the bathin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Facilitation can also be genuinely increased by a desaturation of the release process. In studies of synapses under conditions of little depression and far from saturation of release, it was shown that reducing Ca 2+ influx decreased facilitation and augmentation phases of enhanced release (78)(79)(80)(81). Elevating external [Ca 2+ ] was often, but not always, able to reverse the effects of Ca 2+ channel blockers.…”
Section: Reducing Ca 2+ Influx Reduces Short-term Enhancementmentioning
confidence: 99%
“…Facilitation can also be genuinely increased by a desaturation of the release process. In studies of synapses under conditions of little depression and far from saturation of release, it was shown that reducing Ca 2+ influx decreased facilitation and augmentation phases of enhanced release (78)(79)(80)(81). Elevating external [Ca 2+ ] was often, but not always, able to reverse the effects of Ca 2+ channel blockers.…”
Section: Reducing Ca 2+ Influx Reduces Short-term Enhancementmentioning
confidence: 99%
“…At the NMJ, calcium channels also play a key role in the facilitation of transmitter release (Dudel, 1990; Zengel et al ., 1993a, 1993b). Furthermore, a particular arrangement of calcium channel subtypes and the space–time overlapping of calcium microdomains may also contribute to influence this type of short‐term plasticity (Zucker, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, there is now good evidence that Ca 2+ may play more than one role in the secretory process (e.g., Neher and Zucker, 1993). A multisite action of Ca 2+ would explain previously reported differences in the sensitivities of evoked release and stimulation-induced changes in release to Ba 2 and Sr 2+ and to calcium channel blockers (Zengel, Lee, Sosa, and Mosier, 1993;Zengel, Sosa, and Poage, 1993).…”
Section: Discussionmentioning
confidence: 79%
“…Although the mechanisms underlying the various components of increased release are not known, it has long been thought that Ca 2+ may play a critical role in stimulation-induced changes in release (e.g., Katz and Miledi, 1968;Rosenthal, 1969;Miledi and Thies, 1971;Weinreich, 1971;Erulkar and Rahamimoff, 1978). In support of this, we recently reported that blocking Ca ~+ influx into frog motor nerve terminals with Cd 2+ (Zengel, Lee, Sosa, and Mosier, 1993) or the cone snail peptide ~0-conotoxin (Zengel, Sosa, and Poage, 1993) resulted in a reduction of both facilitation and augmentation, suggesting that Ca 2+ entry may be involved in the generation of these two components of increased release.…”
Section: Introductionmentioning
confidence: 86%